Music Theory System: Phenomenon or Phantom? - Tukova, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of research connects with contemporary state of Ukrainian musicology. Abandoning the guidelines inherited from the Soviet era requires Ukrainian musicologists to rethink a number of positions. In this context, one of the important steps is to correlate the terminology prevailing in Ukrainian musicology with the one that is commonly used in European and American space. One of such specific concepts, which have been established in Ukrainian musicology since the Soviet period, is the music theory system. Its theory was most actively developed in the 1970s and 1980s and entered both scientific circulation and the educational process. At the same time, there is no analogue of this concept and its corresponding theory in European and American musicology. The article is dedicated to analyze of music theory system concept and correlate it with concept of music theory history. The purpose of the article is researching the existing concepts of music theory system, to reveal their originality and correspondence to modern views on the history of Western European music theory. Methods. In the article comparative, systematic and historical research methods are used. The results and conclusions. In Ukrainian musicology original concepts of music theory system presented by I. Kotlyarevskyi and G. Viranovskyi, in Russian musicology such concept was developed by Yu. Kholopov and his scientific school. A detailed study of various approaches to music theory system showed, firstly, their inconsistency among themselves. From the analysis of the researches of G. Viranovskyi and I. Kotlyarevskyi, it follows that both authors have in common the chosen systematic method and the idea of the integrity of music theory system of a certain era. However, both the understanding of the structure of the music theory system and the analytical approaches different. Secondly, the characteristics of music theory systems proposed in the studios of G. Viranovskyi and I. Kotlyarevskyi contradict the currently known factual material. In the case of Viranovskyi, a kind of classical-centric view prevails; in the work of Kotlyarevskyi, the emphasis is mainly on the study of the history of the development of pitch organization indicative for Western European practice. Thirdly, the moscow school investigates purely the history of music theory, the systematic approach is applied only to the generalization of the work of individual authors. The perspective of the study of proposed in the article topic can be seen in the appeal to methods of researching the history of music theory approved by European and American scientific practice, their inclusion in circulation in Ukrainian musicology.